The treatment of melioidosis: is there a role for repurposed drugs? A proposal and review. Issue 12 (2nd December 2019) - Laws, Thomas R; Taylor, Adam W.; Russell, Paul; Williamson, Diane
ABSTRACT: Introduction : Melioidosis is a significant health problem within endemic areas such as Southeast Asia and Northern Australia. The varied presentation of melioidosis and the intrinsic antibiotic resistance of Burkholderia pseudomallei, the causative organism, make melioidosis a difficult infection to manage. Often prolonged courses of antibiotic treatments are required with no guarantee of clinical success. Areas covered : B. pseudomallei is able to enter phagocytic cells, affect immune function, and replicate, via manipulation of the caspase system. An examination of this mechanism, and a look at other factors in the pathogenesis of melioidosis, shows that there are multiple potential points of therapeutic intervention, some of which may be complementary. These include the directed use of antimicrobial compounds, blocking virulence mechanisms, balancing or modulating cytokine responses, and ameliorating sepsis. Expert commentary : There may be therapeutic options derived from drugs in clinical use for unrelated conditions that may have benefit in melioidosis. Key compounds of interest primarily affect the disequilibrium of the cytokine response, and further preclinical work is needed to explore the utility of this approach and encourage the clinical research needed to bring these into beneficial use.